FOMO DAN KEPUTUSAN INVESTASI SAHAM IPO : PERAN LITERASI KEUANGAN DALAM MENGONTROL KEPUTUSAN IMPULSIF - Shakila Ferliana Rachman; Endang Purwaningrum (LPPM STIE Muhammadiah Bandung, 2025)
Stock investments in Initial Public Offerings (IPOs) in the Indonesian capital market are increasingly favored by retail investors, particularly among younger generations. The psychological phenomenon of Fear of Missing Out (FOMO), triggered by social pressure and information spread through social media, can lead investors to make impulsive decisions without analytical consideration. This study aims to analyze the influence of FOMO on IPO stock investment decisions and examine the role of financial literacy in controlling impulsive decisions driven by FOMO. A quantitative approach was employed through an online survey of 142 retail investors who had previously purchased IPO stocks, and the data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). The results show that FOMO has a positive and significant effect on IPO investment decisions, where investors affected by FOMO tend to make quicker and less rational choices. Financial literacy is proven to negatively moderate this relationship, meaning the higher an investor’s level of financial literacy, the lower the influence of FOMO on their investment decisions. The novelty of this research lies in its specific focus on IPO stocks, which have unique characteristics such as limited offering periods, high short-term profit potential, and market euphoria—elements that have not been widely explored in previous FOMO-related studies. The implications of this study highlight the importance of financial literacy education as a safeguard against psychological bias, and as a foundation for regulators and market participants in designing strategies to improve the quality of investment decision-making.